Combined QRS complex and T wave alternans — a new electrocardiographic phenomenon in long QT syndrome: a clinical observation - L. M. Makarov; A. G. Akopyan; V. N. Komolyatova; D. A. Besportochny (Российский кардиологический журнал)
A previously undescribed electrocardiographic pattern is presented in a female patient with long QT syndrome in the form of combined QRS complex and T wave alternans. Possible electrophysiological mechanisms and prognostic value are discussed